Database - Johnson, James L. (Oxford University Press, 1997)
Comprehensive, unique, and accessible, Database: Models, Languages, Design is an ideal text for the introductory computer science course in database theory. It can also serve as a self-study guide for database practitioners. Through his useful organization of the material and his comprehensive, lucid explanations of the concepts, Johnson provides a clear introduction to both traditional and modern topics in database theory. Use of a running example set (an aquarium database) throughout provides a strong sense of continuity